Does Knowledge Sharing Mediates the Relationship between Training and Development on Employee Performance? Case of Food and Beverages Industry - Nur Constance, Wah; Azuriaty, Atang (2024)
The food and beverage industry in Sarawak is dynamic with strong growth prospects driven by local culture, tourism, and a robust agriculture based. The rise of urbanization and the growing of middle to upper class has contributed to the market potential. Recognizing the importance of employee performance in this food and beverages industry, the study seeks to investigate in what way does knowledge sharing mediates the relationship between training and development and employee performance. Using social exchange theory as the underpinning theory, seven hypotheses were tested. The study utilized quantitative method to gather in-depth insights from employees in food and beverage industries. Through statistical analysis, the study examines the direct and indirect effects of training and development on employees performance while examining the mediating effect of knowledge sharing. Quantitative research was employed with online questionnaires were distributed to employees who have undergone training and development. The results suggested that effective training, development and fostering learning culture should be implemented within the food and beverage industry. This study provides improvement of employee performance and contribute to overall business success in the food and beverage industry.